La inconsistente legislación del deporte, en relación a la seguridad del deportista profesional ecuatoriano - Paredes Baños, Oscar Geovanny (2015)
The Social security of the athlete currently does not provide warranties due to the the same as athlete to know and have felt by a reality so demeaning to many athletes live today, is that timely attention is clear and support sports leaders, but essentially does not exist a norm that punish those who fail to comply with this law. It should be noted that the law of sport must ensure athletes who are unable to permanent income, or must take exceptional financial responsibilities, can continue to meet their needs, providing, to that end, financial resources or certain services; payment of life insurance. It must also regulate and implement social policies that guarantee and ensure the welfare of its athletes. Hence the need for this research, where it pretends to expose a reform proposal that collaborate to solve problems of social security of athletes.